Zainteresowanie studentów Uniwersytetu Zielonogórskiego uzyskiwaniem wiedzy o zdrowiu = University of Zielona Gora students` interest in acquiring knowledge about health - Lisicki, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the research conducted in the academic year 2012/2013 was to diagnose the behaviour of full-time first year students of the University of Zielona Gora in relation to the requirements of a healthy lifestyle considered in this work in terms of the interest in acquiring and widening students` knowledge on health.
Keywords: first year students; university; health education; studenci; uniwersytet; edukacja zdrowotna